A Strategic Alliance as an Implementation Strategy to Achieve Ending the HIV Epidemic Goals Among Latino Men Who Have Sex With Men: Florida and Puerto Rico, 2023. - Harkness, Audrey; Reyes, Nequiel; Shrader, Cho-Hee; Tidd, Maeleigh; Altenberg, Nicole; Sánchez, Glorián Carrasquillo; Gerena, Amanda Cruz; Doblecki-Lewis, Susanne; Jaramillo, Jahn; Ledain, Ron; Malavé Rivera, Souhail M.; Martinez, Omar; et al. (American Journal of Public Health, 2026)
Evidence-based interventions for Ending the HIV Epidemic inadequately reach Latino men who have sex with men, particularly in Florida and Puerto Rico, stressing the need for implementation strategies. SOMOS Alianza (San Juan, Orlando, Miami Organizational Strategic Alliance) connects implementers, community members, and researchers pursuing Ending the HIV Epidemic goals among Latino men who have sex with men. We describe SOMOS Alianza, present its post–one-year outcomes, and explore how strategic alliances serve as implementation strategies that reduce HIV disparities.